Penerapan Program Keluarga Harapan Dan Dilematika Bagi Pengentasan Kemiskinan Dikelurahan Teluk Nilau - Salasiah Salasiah; Suhar AM; Lidya Anggraeni (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research is entitled Application of the Family Hope Program and Dilemmas for Poverty Alleviation in Teluk Nilau Village. The research method used by researchers is a qualitative approach. The results of this study were: (1) the mechanism for implementing the PKH program in Teluk Nilau subdistrict was carried out in several stages, namely, regional selection and selection of PKH participants, initial meeting and validation of prospective PKH participants, verification of eligibility, data updating and initial disbursement of funds. PKH in Teluk Nilau Village is aimed at improving the health quality of children under five, pregnant women and the elderly. For the education level of elementary, middle and high school children, the distribution of PKH funds is carried out once a month in 4 stages, namely in January, April, September and December through banks (BNI, BRI and Bank Mandiri). (2) The PKH program in Teluk Nilau sub-district plays an important role in increasing community economic poverty alleviation or KPM PKH including: First, reducing the poverty rate, from the data on the number of PKH beneficiaries from the data the number of recipients is 251 down to 224 in 2021. Second, in the field of education with the PKH program assistance is able to provide an increase in the level of education. Third, in the health sector, the existence of PKH program assistance is able to play a role in increasing poverty alleviation towards improving the level of public health. (3) Regarding the obstacles that were often faced before, it was often the case that recipient cards for the Family Hope program were blocked, but for now this obstacle has almost never happened. Again, this is because the PKH beneficiaries themselves collect the assistance at the post office or bank that has been determined. So for the constraints of the family program, hope has more or less been able to top it.